2014
DOI: 10.1063/1.4884117
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectricity and electrostriction in biocompatible (Na,K)NbO3 nanofiber scaffolds

Abstract: Single phase and highly crystalline biocompatible ferroelectric (Na,K)NbO3 (NKN) nanofibers were synthesized by sol-gel assisted electrospinning technique. Low amplitude piezoelectric response as well as electrostriction effect in NKN fibers were examined using piezoelectric force microscopy technique. Piezoelectric coefficient d33 is strongly anisotropic varying from 75.8 to 18.3 pm/V for, respectively, out-of-axis and on-axis oriented ferroelectric domains in NKN fibers. Hysteresis P-E loop for individual na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…The relative intensity ratios of NKN Bragg reflections I hkl indicate noticeable preferential NKN(001) orientation: I 001 / I 011 = 0.90 in Er:NKN fibers compared to 0.58 in “ideal” Na 0.35 K 0.65 NbO 3 powder . This observation conforms to [001]‐directional cube‐on‐cube growth of nanocrystals in NKN fibers observed earlier in scanning and transmission electron microscope images. Full width at half maximum (FWHM) δ2Θ = 0.34° at 2Θ = 22.6° and δ2Θ = 0.40° at 2Θ = 32.1°, respectively, of (001) and (011) peaks being substituted to Debye‐Scherrer formula yield crystallites’ size of 47.5 and 41.1 nm.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The relative intensity ratios of NKN Bragg reflections I hkl indicate noticeable preferential NKN(001) orientation: I 001 / I 011 = 0.90 in Er:NKN fibers compared to 0.58 in “ideal” Na 0.35 K 0.65 NbO 3 powder . This observation conforms to [001]‐directional cube‐on‐cube growth of nanocrystals in NKN fibers observed earlier in scanning and transmission electron microscope images. Full width at half maximum (FWHM) δ2Θ = 0.34° at 2Θ = 22.6° and δ2Θ = 0.40° at 2Θ = 32.1°, respectively, of (001) and (011) peaks being substituted to Debye‐Scherrer formula yield crystallites’ size of 47.5 and 41.1 nm.…”
Section: Resultssupporting
confidence: 92%
“…Piezoelectric coefficient d 33 was found to be strongly anisotropic varying from 75.8 to 18.3 pm/V in out‐of‐axis and on‐axis oriented ferroelectric domains, correspondingly. Hysteresis P‐E loop yields: coercive field E c = 31 kV/cm, remnant P r = 6.2 μC/cm 2 , and the maximum achieved polarization P max = 21.2 μC/cm 2 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the crystalline nanofibers with a length of 100 μm and diameter 50–200 nm, at room temperature, displayed a spontaneous polarization . Further results, published in a second step, showed that the piezoelectric coefficient d 33 of these nanofibers was strongly anisotropic varying from 75.8 to 18.3 pm V −1 for out‐of‐axis and on‐axis oriented ferroelectric domains, respectively …”
Section: Advanced Synthesis and Properties Of Knn And Related Composimentioning
confidence: 88%
“…Besides commonly used Gd 3+ chelates, Gd 2 O 3 agent can be encapsulated by coaxial electrospinning in biocompatible (Na,K)NbO 3 sheath to form core-shell nanofibers. 11,12 Observed intense room temperature photoluminescence and easy Gd 3+ substitutability by other rare earths (e.g. Tb…”
Section: -8mentioning
confidence: 99%